Answer:
a) The sequence converges to 0
b) The lenght of the curve is [tex]\frac{1}{54}(217^{3/2}-37^{3/2})[/tex]
Step-by-step explanation:
Consider the sequence [tex]a_n = \frac{-6n^6 + \sin^2(7n)}{n^7+11}[/tex]
a) We will prove it using the sandwich lemma. Note that for all n [tex]-1\leq \sin^2(7n)\leq 1 [/tex], then
[tex] \frac{-6n^6 -1}{n^7+11}\leq\frac{-6n^6 + \sin^2(7n)}{n^7+11}\leq \frac{-6n^6 + 1}{n^7+11}[/tex]
Note that the expressions on the left and the right hand side have a greater degree on the denominator than the one on the numerator. Then, by takint the limit n goes to infinty on both sides, we have that
[tex]0 \leq\frac{-6n^6 + \sin^2(7n)}{n^7+11} \leq 0[/tex]
So, the sequence converges to 0.
b) The function [tex]f(x) = 4x^{3/2}+7[/tex] the formula of curve lenght is given by
[tex]s = \int_a^b \sqrt[]{1+(f'(x))^2}dx[/tex]
in this case, a=1, b=6
Note that [tex]f'(x) =6x^{{1/2}[/tex]. Then
[tex]s=\int_1^6 \sqrt[]{1+36x}dx[/tex]. Take u = 1+36x. Then du= 36dx (i.e du/36 = dx). If x = 1, then u = 37 and if x = 6 then u = 217. So,
[tex]s=\frac{1}{36}\int_{37}^{217}\sqrt[]{u} du = \frac{2}{36\cdot 3} \left.u^{3/2}\right|_{37}^{217}=\frac{1}{54}(217^{3/2}-37^{3/2})[/tex]